2002
DOI: 10.1001/archotol.128.9.1058
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of Specific and Total IgE Levels in Allergic Patients After BCG Vaccination

Abstract: BCG, an effective stimulus for cell-mediated immunity, deserves further study to evaluate its ability to modulate the immune response associated with allergic rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…T cells playa critical role in controlling immune responses and they are involved in the inflammatory processes characteristic of allergic diseases. Based on their cytokine production profile helper, T cells (T h) are generally distinguished into two distinct subsets: ThI cells producing IL-2 and IFN-y and T h2 cells producing IL-4, IL-5, IL-6, IL-10, IL-I3 (16)(17). Several studies investigated the cytokine mRNA expression and protein production profiles (ThI versus Th2) of T cell clones and of peripheral mononuclear cells of allergic patients (10,(16)(17)(18)(19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…T cells playa critical role in controlling immune responses and they are involved in the inflammatory processes characteristic of allergic diseases. Based on their cytokine production profile helper, T cells (T h) are generally distinguished into two distinct subsets: ThI cells producing IL-2 and IFN-y and T h2 cells producing IL-4, IL-5, IL-6, IL-10, IL-I3 (16)(17). Several studies investigated the cytokine mRNA expression and protein production profiles (ThI versus Th2) of T cell clones and of peripheral mononuclear cells of allergic patients (10,(16)(17)(18)(19).…”
Section: Resultsmentioning
confidence: 99%
“…These studies showed that allergic diseases are often associated with an increased expression of T h2-like cytokine responses. IL-4 is essential for isotype switching toward IgE, while IL-5 together with IL-4 switches antibody response toward IgA (16)(17). On the other hand, ThI cells have a downregulatory role in the production of T h2 cytokines by releasing IFN-y.…”
Section: Resultsmentioning
confidence: 99%
“…Some insight into the role of IL-21 in allergic responses came from studies showing that exposure to IL-21 resulted in decreased IgE production in an OVA-induced mouse model of allergic rhinitis and in a mouse food allergy model (54,55). In humans, diminution of IgE production has been reported following vaccination with Mycobacterium bovis bacillus Calmette Guerin, BCG (56). This effect has been attributed to the apoptosis of IgE-producing B cells caused by the IL-21 secreted by NKT cells (4).…”
Section: Il-21 In Diseasementioning
confidence: 99%
“…The authors suggested that exposure and response to Mycobacterium tuberculosis may reduce allergic sensitisation. However, additional studies have tested whether immunisation with bacille Calmette-Guérin (BCG) can protect against atopic diseases, but have shown conflicting results [13,14,15,16,17,18]. The discrepancies may be ascribed to the differences in BCG vaccination regimes and bacterial strains used, the populations and age groups studied, the period during which the effects were evaluated, and the pattern of natural exposure to mycobacteria.…”
Section: Introductionmentioning
confidence: 99%